Effects of nanoclay and polyurethanes on inhibition of mild steel corrosion - Banerjee S.; Mishra A.; Singh M.M.; Maiti P. (My University, 2025)
Sulfonated polyurethanes (SPU) were used as corrosion inhibitor for mild steel in acidic solution. The sulfonation of the >N-H groups of the urethane linkages was confirmed from Nuclear Magnetic Resonance (NMR) and Fourier Transform Infra Red (FTIR) spectroscopic techniques. The inhibition efficiency of sulfonated polyurethanes, prepared from two different routes, was investigated using different techniques. The effects of microstructure of polyurethane (PU), degree of sulfonation, time of immersion and temperature on the inhibition of corrosion were discussed. The disc-like nanoparticles, so-called nanoclay, either suspended or chemically attached to SPU chains (nanocomposites) dramatically enhanced the inhibition efficiency for mild steel in acidic medium. All the inhibitors retard the corrosion rate by getting themselves adsorbed on the corroding surface by following the Langmuir adsorption isotherm. The surface analysis of inhibited and uninhibited samples was performed using Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM). Among the various inhibitors used, the nanocomposite of polyurethane was the most effective. Molecular modeling helped in determining the extent of packing of the SPU chains leading to better inhibition efficiency. Copyright © 2011 American Scientific Publishers All rights reserved.